Alexa and the Making of the Neoliberal Ear - Audrey Amsellem (Law Text Culture, 2020)
Smart home device Amazon Echo, equipped with a voice assistant named Alexa, is a new ear within the home, gathering previously inaccessible sounds of the domestic sphere. Devices such as Echo are constantly ‘on’ and listening, but whether Echo is always recording is subject to speculation and ambiguity. In this article, I use Echo to theorise sonic surveillance through what I term the ‘neoliberal ear’– a twenty-first century mode of listening to the world embedded into ‘surveillance capitalism.’ (Zuboff 2019) I examine the relationship between non-creative recording practices and voice-enabled technology within the context of neoliberalism and its legislative allowances. Conceptualizing Amazon Echo as a complex sonic object that listens to voices in the domestic space in order to gather information on the subjectivity of its users while normalizing the ubiquity of listening in, I investigate the surveillance capabilities of the device, and conduct a sound studies analysis of dispossession and displacement in surveillance capitalism, which I argue are rooted in the split between listening and recording in US copyright law. To discuss Echo’s legal ground, I focus on a murder case in which Echo was requested as evidence, considering the specificity of sound within privacy law, and analysing the relationship between Echo and the First and Fourth Amendment of the US Constitution. I view these sonic theorisations of the US legal framework as an initial step to form a neoliberal history of aurality through the conception of the neoliberal ear.